2008
DOI: 10.1177/1087057108320713
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Screening Assay for Small Molecules That Disrupt Yeast Cell Integrity

Abstract: Lead compounds for antifungal drug development are urgently needed because invasive fungal infections are an important cause of morbidity and mortality in immunocompromised patients. Here, a high-throughput screening assay for small molecules that cause yeast cell lysis is described. The assay is based on the detection of the intracellular enzyme adenylate kinase in the culture medium as a reporter of yeast cell lysis. Features of the assay protocol include 1) the ability to detect cell lysis at drug concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…The starting CFU per well was 1.5 ϫ 10 3 , and the MFC was defined as the lowest concentration of compound that reduced the starting inoculum by 2 log 10 . Propidium iodide (PI) staining was performed as described previously (13). All assays were performed on two or three separate days with independent isolates of H99, and each assay was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The starting CFU per well was 1.5 ϫ 10 3 , and the MFC was defined as the lowest concentration of compound that reduced the starting inoculum by 2 log 10 . Propidium iodide (PI) staining was performed as described previously (13). All assays were performed on two or three separate days with independent isolates of H99, and each assay was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The AK assay detects the release of the intracellular enzyme AK into the growth medium by cells that have lost membrane integrity by coupling its conversion of ADP to ATP with a luciferase reporter reaction. We have previously shown that the assay is robust in the HTS setting and is more sensitive than growth assays (8,13). Furthermore, it is specific for molecules that directly kill yeast cells; for example, the fungistatic drug fluconazole is completely inactive in this assay (13).…”
Section: Screen Of Prestwick Library Identifies Drug-like Molecules Withmentioning
confidence: 99%
See 2 more Smart Citations
“…6). Although some effective fungicides exist, like capsofungin, which irreversibly inhibits 1,3-ß-glucan synthase (57), lead compounds are needed to attenuate invasive fungal infections of immunocompromised patients (73), and other potential cell wall targets remain largely unexplored (77). Further characterization of filamentation-dependent cell wall remodeling in budding yeast is likely to provide useful insights into the regulatory inputs of cell wall regulation that may pertain to fungal pathogenesis.…”
Section: Downloaded Frommentioning
confidence: 99%